Data quality deterioration in the Lake Tana Sub-basin, Ethiopia: scoping study to provide streamflow and water withdrawal data - Taye, Meron Teferi; Haile, Alemseged Tamiru; Genet, A.; Geremew, Y.; Wassie, S.; Abebe, B.; Alemayehu, B. (International Water Management Institute, 2022)
This working paper was prepared under a research project from the Future Leaders – African Independent Research (FLAIR) fellowship programme – focusing on understanding hydrological changes in the Lake Tana sub-basin, Ethiopia, due to water abstraction, land use and climate change. FLAIR is funded by the UK government’s Global Challenges Research Fund (GCRF) through The Royal Society, UK. The study was jointly conducted by the International Water Management Institute (IWMI) and staff of the Abbay Basin Development Office (ABDO). The paper provides information on the deterioration of streamflow data quality in the sub-basin. It demonstrates how to support the sub-basin by generating primary data and compiling current water abstraction data that are relevant for development planning. The project showed the possibility of conducting such activities with limited financial resources and time constraints but with strong collaboration. This work also demonstrated the need for a data alliance among stakeholders in the sub-basin.